Constitutional Preview and Review of International Treaties: France And Indonesia Compared - Dewi Nurul Savitri (Constitutional Review, 2019)
The Indonesian Supreme Court and the Indonesian Constitutional Court are experienced in examining international treaties, although the Indonesian constitution and national laws do not stipulate this matter explicitly. The Constitutional Council of France has the authority to examine judicial previews of bills concerning international treaties. Moreover, French judges can examine international treaties. There is also the European Court of Human Rights, which has an important role concerning the control of conventionality. This article aims to promote discussion about the examination of international treaty cases in Indonesia. It begins by considering the international scholarly literature on integrating international treaties and the rank of international treaties in the national legal system. Then, this article discusses the possibility of the Indonesian Constitutional Court to examine judicial preview of international treaty bills and judicial reviews concerning ratified international treaties.